2009
DOI: 10.1002/cncr.24086
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and risk of ovarian cancer

Abstract: Convincing epidemiologic evidence links excess body mass to increased risks of endometrial and postmenopausal breast cancers but the relation of body mass index (BMI) to ovarian cancer risk remains inconclusive. Potential similarities regarding a hormonal mechanism in the etiology of female cancers highlight the importance of investigating associations according to menopausal hormone therapy (MHT) use. However, data addressing whether the relation of BMI to ovarian cancer differs by MHT use are very sparse. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1
14

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 23 publications
2
88
1
14
Order By: Relevance
“…They reported that a 16% increased risk of ovarian cancer for adult overweight and a 30% increased risk for adult obesity when compared with normal weight. Leitzmann et al (2009) also suggested that both overweight and obesity at age 18 years positively associated with ovarian cancer. Both authors concluded that adiposity enhances ovarian cancer risk partly through the mitogenic effects of excess endogenous estrogens synthesized in the adipose tissue.…”
Section: Figure 1 Roc Curve Analysis For Plr In Prediction Of Adolesmentioning
confidence: 97%
“…They reported that a 16% increased risk of ovarian cancer for adult overweight and a 30% increased risk for adult obesity when compared with normal weight. Leitzmann et al (2009) also suggested that both overweight and obesity at age 18 years positively associated with ovarian cancer. Both authors concluded that adiposity enhances ovarian cancer risk partly through the mitogenic effects of excess endogenous estrogens synthesized in the adipose tissue.…”
Section: Figure 1 Roc Curve Analysis For Plr In Prediction Of Adolesmentioning
confidence: 97%
“…No Figure 1) including 10 cohort studies (Engeland et al, 2003;Schouten et al, 2003;Anderson et al, 2004;Niwa et al, 2005;Lacey Jr et al, 2006;Leitzmann et al, 2009;Chionh et al, 2010;Kotsopoulos et al, 2010;Lahmann et al, 2010;Weiderpass et al, 2012) involving 29,237,219 person-years and 9 case-control studies (Riman et al, 2001;Kuper et al, 2002;Beehler et al, 2006;Peterson et al, 2006;Nagle et al, 2008;Olsen et al, 2008;Wernli et al, 2008;Delort et al, 2009;Moorman et al, 2009) involving 96,965 people (Table 1). …”
Section: Description Of Studiesmentioning
confidence: 99%
“…Ovarian cancer accounts for about 4% of all female cancers (Anderson et al, 2004). Its five-year survival rate is 37% (Beehler et al, 2006;Leitzmann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Leitzmann et al (2009a) found that obesity increased the risk of ovarian cancer by nearly 80% in post-menopausal women who had not used menopausal hormonal therapy, but found no such association for those who had.…”
Section: Endometrial Cancer and Ovarian Cancermentioning
confidence: 99%